Analisis Perhitungan BEP sebagai Alat Perencanaan Laba pada Pengecoran Logam Baling-Baling Kapal Wicaksono - Ikhsan Abdul; Jauhari Hadi; Paisal Paisal (Jurnal Terapan Ilmu Ekonomi, Manajemen dan Bisnis, 2023)
This The purpose of this research is to determine the number of break even points required to achieve the minimal limit of sales volume in units and rupiah in the Wicaksono Propeller Brass Metal Casting throughout the previous two years, namely 2021 and 2022. Methods of data collecting included qualitative and quantitative descriptive data kinds, such as interviews, documentation, and literature reviews. The difficulty is that the firm has not categorized fixed and variable expenses, thus the owner cannot utilize the Break Even Point calculation for profit planning, and revenues have been falling for the previous two years. Break Even Point analysis is utilized. Based on the findings of this study, the company's propeller shaft product's break even point is expected to rise between 2021 and 2022. This means that 22% of last year's profit/revenue has to be accounted for in this year' budget